1982
DOI: 10.1159/000182634
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Brain Density in Hemodialysis and Peritoneal Dialysis

Abstract: 30 patients on hemodialysis or peritoneal dialysis have been investigated by computerized tomographic (CT) scan. To evaluate possible cerebral alterations induced by dialysis, CT examinations were carried out before, immediately after and 6 h after the end of dialysis with an Evaluskop, which provides an objective precise evaluation of even slight variations in brain density. No morphological variations were noted after dialysis, while the brain density fell significantly during and after the treatment. A decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…This has been confirmed both at autopsy and by computed tomography imaging of the brain in patients with renal failure who have undergone dialysis (21,22). Several animal models of DDS have been developed and brain swelling has been reported in hemodialyzed dogs (4,23) and rats (14).…”
Section: Discussionmentioning
confidence: 83%
“…This has been confirmed both at autopsy and by computed tomography imaging of the brain in patients with renal failure who have undergone dialysis (21,22). Several animal models of DDS have been developed and brain swelling has been reported in hemodialyzed dogs (4,23) and rats (14).…”
Section: Discussionmentioning
confidence: 83%
“…2), the list also includes cyclic changes in intradialytic hydration. Recent cerebral tono-densitometric studies have refuted a long-held belief and show that tissue density is greater before intermittent dialysis, returning rapidly to a normal level of hydration during dialysis [73]. These fluctuations in the state of hydration, resulting from RDT, are in turn triggered by marked osmotic variations.…”
Section: Brain Circulation and Changes In Brain Tissue Hydrationmentioning
confidence: 97%
“…In addition, enlarged cortical sulci have been reported on cranial CT in up to 80% of pediatric cases with cystinosis (48). Widening of cerebrospinal fluid spaces secondary to brain atrophy (42), with lower cerebral density, has been typically associated with HD (43,49) in comparison with patients receiving continuous ambulatory PD (50). In general, the literature suggested that although brain atrophy was evident in patients with stable CKD and those receiving continuous ambulatory PD, it was definitely more frequent in HD patients.…”
Section: Findings In Pediatric Structural Neuroimaging Studiesmentioning
confidence: 99%